High temperature corrosion of HVOF coatings in laboratory-simulated biomass combustion superheater environments - Pidcock, Andy; Mori, Stefano; Sumner, Joy; Simms, Nigel J.; Nicholls, John R.; Oakey, John (Springer, 2023)
This study examines the fireside corrosion of FeCrAl, NiCr, NiCrAlY and A625 coatings applied by ‘high velocity oxy fuel’(HVOF) and exposed to simulated biomass firing conditions (gas composition CO2, N2, SO2 and HCl). The coatings and a typical base steel alloy (T92) were exposed to simulated conditions at 600 °C for 1000 h in a laboratory scale furnace. Samples were coated with a potassium chloride deposit. Samples were then cold mounted in a low-shrinkage epoxy resin and then cross-sectioned. Corrosion was assessed by dimensional metrology comparing the coating thickness change of the samples. The cross-sections of the ‘worst’ and ‘best’ coatings were examined. Results show that all but one coating (HVOF NiCr) outperformed the T92 alloy. No coating composition or method was conclusively better. Evidence of Cr depletion as well as the formation of a sulphidation layer have been found in the exposed samples with coatings. The formation of a K2SO4 layer has also been observed on all coated specimens.
Keywords: Metal coatings; Molten salts; High temperature corrosion; Fireside corrosion